2014
DOI: 10.1111/cei.12256
|View full text |Cite
|
Sign up to set email alerts
|

Increased 8-hydroxy-2′-deoxyguanosine in plasma and decreased mRNA expression of human 8-oxoguanine DNA glycosylase 1, anti-oxidant enzymes, mitochondrial biogenesis-related proteins and glycolytic enzymes in leucocytes in patients with systemic lupus erythematosus

Abstract: SummaryWe measured plasma levels of the oxidative DNA damage marker 8-hydroxy-2′-deoxyguanosine (8-OHdG) and leucocyte mRNA expression levels of the genes encoding the 8-OHdG repair enzyme human 8-oxoguanine DNA glycosylase 1 (hOGG1), the anti-oxidant enzymes copper/zinc superoxide dismutase (Cu/ZnSOD), manganese superoxide dismutase (MnSOD), catalase, glutathione peroxidase-1 (GPx-1), GPx-4, glutathione reductase (GR) and glutathione synthetase (GS), the mitochondrial biogenesis-related proteins mtDNA-encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…The majority of the SLE patients included in this metabolomics study were of AA and Hispanic-American ancestry. In another study, lower mRNA expression of the genes encoding glycolytic enzymes has been shown in the leukocytes of Asian SLE patients as compared to controls [42]. It is currently unclear why this reduction in metabolic pathway activation in SLE blood is observed, but it has been independently shown in a number of studies, including the present one.…”
Section: Discussionsupporting
confidence: 53%
“…The majority of the SLE patients included in this metabolomics study were of AA and Hispanic-American ancestry. In another study, lower mRNA expression of the genes encoding glycolytic enzymes has been shown in the leukocytes of Asian SLE patients as compared to controls [42]. It is currently unclear why this reduction in metabolic pathway activation in SLE blood is observed, but it has been independently shown in a number of studies, including the present one.…”
Section: Discussionsupporting
confidence: 53%
“…However, this increase was abrogated in Ogg1 −/− Nlrp3 −/− BM chimeric mice, suggesting that the mechanism by which Ogg1 deficiency leads to accelerated atherogenesis is at least in part through the NLRP3 inflammasome. While some human Ogg1 polymorphisms have been linked with various pathologies such as large artery atherosclerotic stroke in smokers 44 and SLE severity 45, 46 , no studies have yet demonstrated its role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 8-OH-dG accumulation in mtDNA is increased 20-fold in livers of Ogg1 −/− mice compared to WT mice 59 . The human Ser326Cys (C8055G) OGG1 polymorphism is associated with decreased repair activity 60 and is linked to large artery atherosclerotic stroke in smokers 44 ; the C1245G polymorphism correlates with increased 8-OH-dG in leukocyte DNA and more severe manifestations of systemic lupus erythematosus (SLE) 45, 46 . Atherosclerosis is a well-recognized complication of SLE, but underlying mechanisms are complex and remain areas of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly assessed markers for oxidative stress are lipid oxidation products such as 8-isoprostane and malondialdehyde, and DNA oxidation products such as 8-hydroxy-2-deoxyguanosine (8-oxo-dG) which can be measured in blood and/or urine [33]. The activity of antioxidant enzymes, e.g., glutathione peroxidase or catalase, can also provide information regarding oxidative stress [34]. While multiple biomarkers have been developed that measure various types of oxidative stress, there are unresolved challenges in devising accurate and reproducible assays that can be applied to human studies [24,25].…”
Section: Resultsmentioning
confidence: 99%